Penyakit Kaki, Tangan, dan Mulut dan Pengobatannya - Ilma Nugrahani (JURNAL ILMU KEFARMASIAN INDONESIA, 2005)
Information related to cause, spreading, prevention, and symptomatic treatment of Handfoot-and-mouth disease (HFMD) has been compiled. It is a viral illness with a distinct clinical presentation of oral and distal extremity lesions characteristic. Most commonly, the etiologic agent are coxsackieviruses, members of Picornaviridae family, namely coxcackievirus A16 or enterovirus 71. The drugs used to symptomatic care are anesthetic agent, antipyretic, analgesic, antihistamine, antacid, and antiseptic agent.